A SIMULATION OF IRRADIATION CALCULATIONS ON LUTETIUM-177 PRODUCTION IN RSG-GAS USING U3SI2-AL AND U9MO-AL FUELS - Lena Rosmayani; Anis Rohanda; Raden Farzand Abdullatif (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2023)
This research is a simulation of irradiation calculations on the production of the radioisotope Lutetium-177 (177Lu) in the G.A Siwabessy Reactor (RSG-GAS). This study aims to analyze the comparative calculation of 177Lu activity and its purity. One of the production methods of 177Lu in RSG-GAS is carried out by irradiating Lu2O3 targets. This Lu2O3 target irradiation produced the radioisotope 177Lu along with 177mLu as an impurity. For Medical treatment using radioisotopes, the minimum activity for 177Lu is 20 GBq/mg, and the impurity should not exceed 0.1%. Calculations were carried out with thermal neutron flux input at 15 MWt operational power for the RSG-GAS core with U3Si2-Al fuel (density 2.96 gU/cc and 3.55 gU/cc) and U9Mo-Al fuel (density 3.55 gU/cc). Calculations were carried out by simulating 8 days of irradiation using ORIGEN2.1. The results showed that the 177Lu activity resulting from irradiation of Lu2O3 targets at various CIP positions in the U9Mo-Al reactor core was larger than that of the U3Si2-Al core. Until the 30th day, the 177Lu product resulting from irradiation on the U3Si2-Al and U9Mo-Al cores still meets the minimum value of 20 GBq/mg for treatment needs in nuclear medicine, with the activity value of 177Lu resulting from irradiation on the U3Si2-Al core ranging from 241-403 GBq/mg, while the activity of irradiated 177Lu in the U9Mo-Al core ranges from 335-561 GBq/mg. In addition, until the 30th day of decay, 177Lu has a percentage value of 177mLu irradiated in the U9Mo-Al and U3Si2-Al cores of 0.0346% and 0.0344%, respectively. The results are still below the maximum impurity value of 0.1% and thus safe to use as a therapeutic agent.Â Keywords:Â 177Lu, Activity, RSG-GAS, ORIGEN2, Irradiation